PENINGKATAN PRODUKTIVITAS PADI DI PROVINSI RIAU MELALUI PERBAIKAN SISTEM TANAM - Masganti Masganti (Al-Ulum, 2021)
High population growth and low consumption of carbohydrate sources in Riau Province encourage rice production to be increased. One effort to increase rice production in Bumi Lancang Kuning is to increase productivity through improved planting systems. The research was conducted in the rainy season of 2016 on irrigated and tidal paddy field using Inpari 13 variety, aiming to determine the best planting system in increasing Riau Province rice productivity. Irrigated rice field is located in Dayang Suri Village, Bunga Raya Subdistrict, and tidal land is located in Selat Guntung Village, Sabak Auh Subdistrict, Siak Regency, Riau Province. The three planting systems tested were (1) tiles, (2) Jarwo 4: 1, and (3) Jarwo 2: 1 and two agroecosystems ie (a) tidal land and (b) irrigated land. The treatment was arranged in a randomized block design (RBD) with five replications. Fertilization N, P2O5, and K2O for irrigated land (67.5-60-45) and tides (90-120-60). The parameters observed were plant height and number of tillers 30 and 60 days after planting (DAP), number of grain per panicle, weight of 1,000 grains, and rice productivity (t/ha). The results showed that plant height and number of tillers of 30 DAP were not affected by treatment, while the plant height, number of tillers at 60 DAP, the number of grains per panicle, and the weight of 1,000 grains were affected only by agro-ecosystem. Rice productivity is strongly influenced by agro-ecosystem and planting system. The productivity of rice in tidal land is lower than irrigated land. Compared with tile planting systems, the increased productivity of the Jarwo 2: 1 planting system is higher than the Jarwo 4: 1 planting system. Increased productivity due to improved planting systems in tidal areas is higher than irrigated land.